2022
DOI: 10.1155/2022/1495082
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in miR146a, an Inflammation-Associated MicroRNA, with the Risk of Idiopathic Recurrent Spontaneous Miscarriage: A Case-Control Study

Abstract: It has been established that microRNAs (miRNAs) are involved in the regulation of immune responses and serve as biomarkers of inflammatory diseases as well as recurrent spontaneous miscarriage (RSM). Herein, we aimed to study the relationship between three functional miR146a gene polymorphisms with idiopathic RSM (IRSM) susceptibility. We recruited 161 patients with IRSM and 177 healthy women with at least one live birth and without a history of abortion. Genotyping was performed using RFLP-PCR and ARMS-PCR me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…More than 65 genetic variants in 45 genes were identified that could be considered as risk factors for iRPL (Table 1). 13–59 The time frame of the sample is not mentioned in the studies because it does not involve a variable marker. Epigenetic factors, mainly microRNAs (miRNAs), that could also be considered as risk factors are compiled in Table 2 60–64 .…”
Section: Resultsmentioning
confidence: 99%
“…More than 65 genetic variants in 45 genes were identified that could be considered as risk factors for iRPL (Table 1). 13–59 The time frame of the sample is not mentioned in the studies because it does not involve a variable marker. Epigenetic factors, mainly microRNAs (miRNAs), that could also be considered as risk factors are compiled in Table 2 60–64 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the observed ncRNA expression levels and their related potential mechanisms of action in GO pathogenesis. Among the ncRNAs implicated in inflammatory regulation was miR-146a [ 80 , 81 ], LPAL2/miR-1287–5p axis, LINC01820:13/has-miR-27b-3p axis, and ENST00000499452/hsa-miR-27a-3p axis ( Fig. 4 a).…”
Section: Resultsmentioning
confidence: 99%
“…A recent exome sequencing study on a cohort of POC indicated that genes with dominant effect on multisystem abnormalities, neurodevelopmental disorders, cardiac anomalies, skeletal dysplasia, metabolic disorders, and renal diseases could cause SAB (Zhao et al, 2021 ). Furthermore, maternal genetic polymorphisms and fetal microRNA polymorphisms associating with immunological responses, thrombophilia, abnormal placental function, and disturbance of metabolic regulation could have a modifying effect on the penetrance of SAB for chromosomal abnormalities and pCNVs (Salimi et al, 2022 ; Shi et al, 2017 ).An integrated approach should be applied to elucidate the dosage‐sensitive effect, dominant lethal conditions, genetic modifiers, and epigenetic changes related to pregnancy losses.…”
Section: Discussionmentioning
confidence: 99%